2021
DOI: 10.1001/jamacardio.2020.6897
|View full text |Cite
|
Sign up to set email alerts
|

To DOAC or Not to DOAC for Left Ventricular Thrombi—What Is the Dose?—Reply

Abstract: Williams JB, McConnell G, Allender JE, et al. One-year results from the first US-based enhanced recovery after cardiac surgery (ERAS Cardiac) program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In response, Robinson et al reported only 4 of 73 (5%) patients treated with apixaban were treated with the low-dose regimen and none developed stroke and that all anticoagulation interruptions were accounted for in the time dependent analysis. Despite these adjustments, DOAC use remained a predictor of SSE [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In response, Robinson et al reported only 4 of 73 (5%) patients treated with apixaban were treated with the low-dose regimen and none developed stroke and that all anticoagulation interruptions were accounted for in the time dependent analysis. Despite these adjustments, DOAC use remained a predictor of SSE [ 30 ].…”
Section: Discussionmentioning
confidence: 99%